2004
DOI: 10.1017/s1350482704001288
|View full text |Cite
|
Sign up to set email alerts
|

Sky view factor analysis – implications for urban air temperature differences

Abstract: This study identifies the use of the sky view factor (SVF)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
1
14

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(115 citation statements)
references
References 26 publications
7
93
1
14
Order By: Relevance
“…Since one of the stated aims of the present study was to attempt to exclude the distance-from-centre factor, the use of relatively small source areas was crucial. In line with Svensson's (2004) findings, the results of this study show no improvement in R 2 between T a and SVF at sensor height (2 m) when compared with the SVF at ground level.…”
Section: Urban Surface Parameters and Temperature Variationssupporting
confidence: 89%
See 1 more Smart Citation
“…Since one of the stated aims of the present study was to attempt to exclude the distance-from-centre factor, the use of relatively small source areas was crucial. In line with Svensson's (2004) findings, the results of this study show no improvement in R 2 between T a and SVF at sensor height (2 m) when compared with the SVF at ground level.…”
Section: Urban Surface Parameters and Temperature Variationssupporting
confidence: 89%
“…Both the surface and air temperatures within the city of Göteborg have been studied in relation to geometry for a long time (e.g. Eliasson, 1996;Upmanis, 1999;Lindberg, 2002;Lindberg et al, 2003;Svensson, 2004). These studies show that the surface and air temperatures generally decrease with increasing SVF.…”
Section: Urban Geometry and Intra-urban Temperature Variationsmentioning
confidence: 99%
“…Others adopt a three-dimensional approach by examining the impact of sky view factor which is the amount of free sky uninterrupted by buildings, structures, or vegetation at a specific location [23][24][25][26][27][28]. A second focus is on urban density.…”
Section: Introductionmentioning
confidence: 99%
“…Gál et al (2009) reported a strong linear negative association between annual mean temperatures and SVF. Other studies also showed statistically significant associations between SVF and urban temperature (Chen et al, 2012;Unger, 2009;Svensson, 2004). …”
Section: Literature Reviewmentioning
confidence: 81%